The Impact of Daily Mindfulness Practice and Meditation on Stress Reduction and Improvement in Quality of Life in Indonesia - Arisanti, Ivon; Mubarok, Ahmad Shofi (The Eastasouth Journal of Social Science and Humanities, 2024)
This study investigates the impact of daily mindfulness practice and meditation on stress reduction and quality of life improvement among individuals in Indonesia. Using a quantitative research approach, data were collected from 230 participants through a structured questionnaire, with responses measured on a Likert scale. Structural Equation Modeling (SEM) using Partial Least Squares (PLS) was employed to analyze the relationships between mindfulness, meditation, stress reduction, and quality of life. The results revealed that daily mindfulness practice and meditation significantly positively affect stress reduction and quality of life improvement. Meditation demonstrated a stronger effect on stress reduction, while mindfulness showed a slightly higher impact on overall quality of life. These findings highlight the importance of integrating mindfulness and meditation into mental health interventions to promote well-being and manage stress effectively. This research contributes to the growing body of evidence supporting mindfulness-based practices and offers valuable insights for mental health professionals and policymakers in Indonesia.